Studies on the growth and essential oil accumulation of Elsholtzia ciliate (Thunb.) Hyland and the effect of gibberellic acid treatment on growth and essential oil accumulation - Luong Thi Le Tho; Luu Tang Phuc Khang; Nguyen Xuan Hieu; Dinh Thi Bich Thuy; Vo Ngoc Khoi Nguyen; Chau Minh Hai Dang; Tran Thi Phuong Dung (Vietnam Journal of Science, Technology and Engineering, 2024)
Vietnamese balm (Elsholtzia ciliata (Thunb.) Hyland) (E. ciliata) is known as an aromatic herb and a valuable remedy in oriental medicine thanks to the essential oil contained in the leaves. In plant life, plant growth regulators play an important role in the growth and accumulation of essential oils. This article investigates the effect of gibberellic acid (GA3) on the growth and essential oil accumulation of E. ciliata at the 4-week-old plant stage based on a randomised complete block design with 3 replications. The results showed that the effect of GA3 (0, 5, 10, 15, 20, and 25 ppm) on growth parameters of E. ciliata. GA3 increases plant height, leaf length, leaf width, whole plant fresh weight, dry weight, nitrate content, and essential oil percentage significantly (p≤0.05). With an increasing amount of GA3, all of these parameters increased significantly compared to the control. The treatment with 10 ppm GA3 resulted in the highest plant height, leaf length, leaf width, and production of fresh weight, dry weights, nitrate content, and more than the control. The highest essential oil yield (1.41%) was obtained by applying 10 ppm GA3. The results of this study showed that the quantitative and qualitative yield of Vietnamese balm could be increased by treatment with an appropriate amount of gibberellic acid.